(untitled) (GYMNASIUM, 2009)
We created an experimental model drawn a specialty literature, to study muscular fatigue. We used both research methods surface electromiography and mechanogram. We observed that the shorter muscular contractions and rest intervals are the later muscular fatigue onset in a reasonable time. The duration of muscular contractions and rest intervals influence physical effort intensity. Briefly, I succeeded in creating muscular fatigue quantification by using several physiological parameters.